The effect of multi-arc ion plating NiCr coating on interface characterization of ZrO₂-Al₂O₃ ceramics reinforced iron-based composites - Li, Cong (2022)
The ZrO2–Al2O3 (ZTA) ceramic particles reinforced iron matrix composite was a novel wear-resistance material because of their excellent toughness and hardness. However, the poor interfacial bonding property restricted the application of ZTAP/Fe composites in the harsh service condition. A continuous and uniform Ni80Cr20 coating on the ZTA ceramic surface was successfully prepared by multi-arc ion plating. The influence of NiCr coating on the interfacial character of ZTAP/Fe composites was investigated. The interface characteristics and phase constitutions of ZTAP/Fe composites were also analyzed by electron probe microanalysis (EPMA) and transmission electron microscopy (TEM). The results showed that the Ni80Cr20 coating can significantly improve the interfacial layer bonding of composites without visible defects. The diffusion of Ni and Cr and the formation of a continuous transition layer ensure the metallurgical bonding between ZTA ceramic and iron matrix. The composite N1 acquired better wear resistance than that of composite N2 without Ni80Cr20 coating, and the relative wear resistance was 1.98 times at the 55 N applied load. The interface of composite N1 was closely bonded with a transition layer, which may prevent the ceramic particles peeling off from the iron matrix during the wear process.